2022
DOI: 10.18103/mra.v10i7.2917
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometrics and Myocardial Infarction Risk: A Misleading Evidence Was Accepted by Cardiovascular Sciences When Errors of Bias Were Overlooked Worldwide. When Should We End Discussion about the Optimal Metric?

Abstract: Despite the impact of the COVID‑19 pandemic, myocardial infarction remains the leading cause of cardiovascular deaths in Europe. Body mass index (BMI)-defined obesity is a major risk factor for myocardial infarction. However, in the association of anthropometrics and myocardial infarction, the lack of balance between the simple body measurements when comparing healthy and unhealthy cases has demonstrated that affects the outcome. Thus, regardless of association strength of anthropometrics, other criteria to ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
110
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(112 citation statements)
references
References 28 publications
2
110
0
Order By: Relevance
“…Thus, either for HC-WC or HCheight/2, the imbalance was significantly slanted toward one of the groups with a mean |x|>0, and it created a protective overestimation of HC with respect to WC and height 8,9,20,26 (see Table 2). This mathematically demonstrated that any WHRassociated risk beyond that of WC and WHtR was a spurious-risk providing a false causal inference, and was anthropometrically impossible 8,9,20,26,33 20 . In this situation, and since in healthy people WC usually is lower than height/2 (see Table 1), the imbalance with a mean |x|>0 was significantly slanted towards the cases status, creating a risk overestimation for WC in the tallest people and an underestimation in the shortest.…”
Section: Recent Findings and Paradigm Shift On The Associations Of An...mentioning
confidence: 94%
See 4 more Smart Citations
“…Thus, either for HC-WC or HCheight/2, the imbalance was significantly slanted toward one of the groups with a mean |x|>0, and it created a protective overestimation of HC with respect to WC and height 8,9,20,26 (see Table 2). This mathematically demonstrated that any WHRassociated risk beyond that of WC and WHtR was a spurious-risk providing a false causal inference, and was anthropometrically impossible 8,9,20,26,33 20 . In this situation, and since in healthy people WC usually is lower than height/2 (see Table 1), the imbalance with a mean |x|>0 was significantly slanted towards the cases status, creating a risk overestimation for WC in the tallest people and an underestimation in the shortest.…”
Section: Recent Findings and Paradigm Shift On The Associations Of An...mentioning
confidence: 94%
“…However, this situation epidemiologically never happens. By contrast, in any WHtR risk cut-off >0.5, area and volume measurements will never mathematically express the same whole-risk nor the same whole-body fat percentage 8,9,27,28,33 . Thus, when assigning true risk, only WHtR from a risk cutoff above 0.5 better captures a high-risk BC 8,9,17,28,33 (see Figure 1).…”
Section: Recent Findings and Paradigm Shift On The Associations Of An...mentioning
confidence: 98%
See 3 more Smart Citations